2020
DOI: 10.1016/j.dr.2020.100934
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal depression and anxiety and offspring infant negative affectivity: A systematic review and meta-analysis

Abstract: Maternal internalizing symptoms during pregnancy, specifically depression and/or anxiety, are commonly linked to negative affectivity (NA) in infant offspring. These links are commonly attributed to biological effects of the in utero environment on fetal development. However, research suggests that internalizing symptoms before and after pregnancy, as well as in fathers, may also be associated with NA in infant offspring. Such findings suggest greater complexity in transmission than can be explained by biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 125 publications
5
10
0
Order By: Relevance
“…Further, small standardised effects can correspond to meaningful real-life differences; for example, in fathers, the observed standardized beta of 0.18 corresponds to an AUD $12,488 increase in income for every standard deviation increase in emotional stability. Moreover, we found large effect sizes when considering a binary exposure of extreme versus normative personality trait levels, with effect sizes similar to those commonly observed for proximal and concurrent parental exposures 69 , 70 , a striking finding given our more distal assessment of personality up to 10 years preconception.…”
Section: Discussionsupporting
confidence: 83%
“…Further, small standardised effects can correspond to meaningful real-life differences; for example, in fathers, the observed standardized beta of 0.18 corresponds to an AUD $12,488 increase in income for every standard deviation increase in emotional stability. Moreover, we found large effect sizes when considering a binary exposure of extreme versus normative personality trait levels, with effect sizes similar to those commonly observed for proximal and concurrent parental exposures 69 , 70 , a striking finding given our more distal assessment of personality up to 10 years preconception.…”
Section: Discussionsupporting
confidence: 83%
“…Recent work in perinatology and developmental psychopathology converge on the suggestion that a mother’s emotional experience while pregnant and in the first years of life influences her child’s long-term development, including elevated risk for neurodevelopmental and behavioral problems from infancy to adolescence (see Van den Bergh et al, 2017 for review). For example, pre- and early postnatal maternal emotion marked by anxiety has been linked to infant negative affect and childhood internalizing symptoms (e.g., Lawrence, Creswell, Cooper, & Murray, 2020 ; Spry et al, 2020 ). These effects likely vary by the type, timing, and intensity of a pregnant woman’s pre- or postnatal emotional experience, which itself may be exacerbated by other stressors, such as substance use and poverty (e.g., Eiden et al, 2011 ).…”
mentioning
confidence: 99%
“…One of the few longitudinal studies that analyzed this predictive path between parental anxiety and youth-internalizing symptoms reached the same conclusion (Johnco et al, 2021). Further research on paternal anxiety is necessary, as the vast majority of the samples included a higher percentage of mothers than fathers (Spry et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…In recent years, studies have highlighted the importance of analyzing the effects of other psychological disorders, such as anxiety (Goodman, 2020). Parental anxiety is a predictor of a youth's internalizing symptoms (Spry et al, 2020). A meta-analysis has concluded that parental anxiety is a risk factor for youth in developing internalizing symptoms related to anxiety and depression disorders (Möller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%